Intellectual Property and Development : Lessons from Recent Economic Research - Fink, Carsten; Maskus, Keith E. (Washington, DC: World Bank and Oxford University Press, 2012)
How will developing countries fare in this new international environment? This book brings together empirical research that assesses the effects of changing intellectual property regimes on various measures of economic and social performance-ranging from international trade, foreign investment and competition to innovation and access to new technologies. The studies presented point to an important development dimension to the protection of intellectual property. But a one-size fits all approach to intellectual property is unlikely to work. There is need to adjust intellectual property norms to domestic needs, taking into account developing countries' capacity to innovate, technological needs, and institutional capabilities. In addition, governments need to consider a range of complementary policies to maximize the benefits and reduce the costs of reformed intellectual property regulations.